Control of catalytic flow reversal reactors - Aw, You Wei (2009)
Catalytic flow reversal reactor (CFRR) is a special type of reactor that traps heat generated by exothermic reactions and utilizes the heat to preheat the feed. To do so, it reverses the feed flow direction periodically. However, without an effective control system in place to control the amount of heat in the reactor, the CFRR can either extinguish or overheat if feed conditions are extreme and prolonged. Thus, an effective control system must be implemented.